2018
DOI: 10.58327/jstfi.v5i2.58
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI KRIM SARI BUAH STROBERI (Fragaria X ananassa D.) SEBAGAI ANTIOKSIDAN

Abstract: Buah stroberi (Fragaria X ananassa D.) diketahui memiliki banyak manfaat yang luar biasa bagi kesehatan tubuh, terutama sebagai antioksidan. Penelitian ini bertujuan untuk membuat sediaan krim yang mengandung sari buah stroberi yang dapat memberikan efek antioksidan dan memiliki stabilitas yang baik. Formula krim dibuat dengan konsentrasi sari buah stroberi 0,015 %, 0,15 %, dan 0.30 % dengan komposisi asam stearat 20%, setil alkohol 1%, propilenglikol 10%, trietanolamin 2%, gliserin 10%, nipagin 0.10 %, nipaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
1
Order By: Relevance
“…Based on previous research by Rinandari et al (2021) where clinical trial research was conducted on humans by administering 4% HQ cream for 8 weeks with MASI (Melasma Area and Severity Index) evaluation to assess the severity of melasma carried out at week 4 and week 8, the melasma lesions experienced significant changes at week 4 and week 8 (Rinandari et al, 2021). Other previous in vitro research found that 0.3% strawberry juice cream (Fragaria ananassa) is a strong antioxidant with an IC 50 antioxidant capacity of 52.59 ppm (Ferdiansyah et al, 2016). The use of 12.5% strawberry ethanol extract cream in this research is based on previous studies that 12.5% strawberry ethanol extract cream meets control and quality test standards, which consist of organoleptic, pH test, spreadability test, stickness test and protective capacity test (Arifah et al, 2013).…”
Section: Effects Of Administration Of 125% Strawberry Ethanol Extract...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research by Rinandari et al (2021) where clinical trial research was conducted on humans by administering 4% HQ cream for 8 weeks with MASI (Melasma Area and Severity Index) evaluation to assess the severity of melasma carried out at week 4 and week 8, the melasma lesions experienced significant changes at week 4 and week 8 (Rinandari et al, 2021). Other previous in vitro research found that 0.3% strawberry juice cream (Fragaria ananassa) is a strong antioxidant with an IC 50 antioxidant capacity of 52.59 ppm (Ferdiansyah et al, 2016). The use of 12.5% strawberry ethanol extract cream in this research is based on previous studies that 12.5% strawberry ethanol extract cream meets control and quality test standards, which consist of organoleptic, pH test, spreadability test, stickness test and protective capacity test (Arifah et al, 2013).…”
Section: Effects Of Administration Of 125% Strawberry Ethanol Extract...mentioning
confidence: 99%
“…Based on previous in vitro research, it was proven that 0.3% strawberry (Fragaria ananassa) juice cream has an antioxidant capacity with an IC 50 (Inhibition Concentration) value of 52.59 ppm and is classified as a strong antioxidant (Ferdiansyah et al, 2016). In vitro research by Widyastuti and Primagara found that the ethanol extract of strawberry (Fragaria ananassa) consisting of flavonoids, phenolics and saponins has the ability to act as a sunscreen and tyrosinase inhibitor (Widyastuti & Primagara, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Komponen-komponen yang terkandung dalam biji pinang seperti arekain, arekolin, guvalokin, guvasine, arekolidine, dan isoguvasine. Sari etanol dari biji pinang juga mengandung flavan, senyawa fenolik, tanin yang mengalami perubahan wujud, tannin yang mengalami penguraian zat, minyak yang dapat menguap dan tidak menguap, asam glanat, lignin, serta getah (Ferdiansyah et al, 2016). Kehadiran efek ini membuka peluang dikembangkannya pinang (Areca catechu L.) sebagai agen antischistosomiasis (Dewi, Pakaya, & Tandi, 2021).…”
Section: Pembahasanunclassified
“…Aktivitas antioksidan sari buah stroberi ini berkaitan dengan senyawa antosianin yang terkandung di dalamnya. Formulasi sediaan krim ini meliputi stearate acid 12%, setil alkohol 0,6%, propilenglikol 6%, metil paraben 0,06%, trietanolamin 1,2%, gliserin 6%, propil paraben 0,03%, sari buah stroberi 0,009% dan akuades ad 60 [39].…”
Section: Hasil Dan Pembahasanunclassified